ERiSA: building emotionally realistic social game-agents companions - Chowanda, Andry; Blanchfield, Peter; Flintham, Martin D.; Valstar, Michel (Springer Verlag, 2014)
We propose an integrated framework for social and emotional game-agents to enhance their believability and quality of interaction, in particular by allowing an agent to forge social relations and make appropriate use of social signals. The framework is modular including sensing, interpretation, behaviour generation, and game components. We propose a generic formulation of action selection rules based on observed social and emotional signals, the agent’s personality, and the social relation between agent and player. The rules are formulated such that its variables can easily be obtained from real data. We illustrate and evaluate our framework using a simple social game called The Smile Game.